Pengaruh Independent Board of Commissioners, Institutional Ownership, and Audit Committee terhadap Firm Value - Yohanes Mardinata Rusli; Piter Nainggolan; Juan Carlos Pangestu (Universitas Bunda Mulia, 2020)
High company value is the expectation of company owners, because with high value shows the prosperity of shareholders is also high so that shareholders will invest their capital in the company. This can be done by implementing governance that is expected to increase the value of the company through increasing shareholders. This article examines the influence of Independent board of commissioners, Institutional Ownership, and Audit Committees on Firm Value. This research was conducted by collecting corporate data obtained from the financial statements of manufacturing industry companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in the period 2016 to 2018 with a sample of 25 companies with observations for 3 (three) years using a purposive sampling method that aims to get a representative sample in accordance with the criteria determined by researchers. The total data processed is 75 units of analysis data. The type of data used is secondary data in the form of company annual reports. The testing tool used is Eviews 9 which consists of Descriptive Statistics Test, Classic Assumption Test, Model Selection Test, and Hypothesis Test. The results showed that the results of selecting the right model for this study were the Random Effect Model (REM). The results of this study indicate that, Independent board of commissioners and Institutional Ownership have no effect on Firm Value. While the results of other studies indicate that the Audit Committee influences Firm Value. Based on the results of this study, companies are expected to pay more attention to the existence of independent commissioners, audit committees and institutional ownership to strengthen good governance and consider investing in one company. Keywords: Independent board of commissioners, Intitutional Ownership, Audit Committee, Firm Value ABSTRAK Nilai perusahaan yang tinggi menjadi harapan para pemilik perusahaan, sebab dengan nilai yang tinggi menunjukan kemakmuran pemegang saham juga tinggi sehingga pemegang saham akan menginvestasikan modalnya kepada perusahaan tersebut. Artikel ini meneliti mengenai pengaruh dari Independent board of commissioners, Intitutional Ownership, dan Audit Committee terhadap Firm Value. Penelitian ini dilakukan dengan mengumpulkan data data perusahaan yang diperoleh dari laporan keuangan perusahaan industri manufaktur pada sektor barang konsumsi yang tercatat dalam Bursa Efek Indonesia (BEI) pada periode tahun 2016 sampai tahun 2018 dengan jumlah sampel perusahaan sebesar 25 perusahaan dengan menggunakan metode purposive sampling yang bertujuan untuk mendapatkan sampel yang representatif sesuai dengan kriteria yang ditentukan peneliti. Jenis data yang digunakan yaitu data sekunder berupa laporan tahunan perusahaan. Alat pengujian yang digunakan yaitu Eviews 9 yang terdiri dari pengujian Uji Statistik Deskriptif, Uji Asumsi Klasik, Uji Pemilihan Model, dan Uji Hipotesis. Hasil penelitian menunjukan bahwa hasil dari pemilihan model yang tepat untuk penelitian ini adalah Random Effect Model (REM). Hasil penelitian ini menunjukan bahwa, Independent board of commissioners dan Intitutional Ownership tidak berpengaruh terhadap Firm Value. Sedangakan hasil penelitian lainnya menunjukan bahwa Audit Committee berpengaruh terhadap Firm Value. Berdasarkan hasil penelitian ini, perusahaan diharapkan lebih memperhatikan keberadaan komisaris independent, komite audit dan kepemilikan institusional untuk memperkuat tata kelola yang baik dan mempertimbangkan dalam melakukan investasi di satu perusahaan.